KONSEP PENDIDIKAN ISLAM DALAM MEMBENTUK PRIBADI ANAK YANG SHALIHAH - Ulin Nadlifah Ummul Khoir (Prodi PGMI IAIN Salatiga, 2009)
Noble character is a reflection of one's personality, in addition to the superior morality will be able to bring someone to the high dignity. Lately, a good manner is costly and hard to find. The lack of understanding of moral values contained in the Qur'an and Hadith will further aggravate the condition of a person's personality, even life seemed to feel less meaningful. To form a noble personal, moral cultivation against children should be encouraged from an early age, since its formation will be easier than after the child's adulthood. Al Akhlaq Lil Banat book discusses some manners to apply in life, good family environment, school or community. It will create private-mannered accordance with the guidance of the Qur'an. It is a kind of literature review. To obtain representative data in the discussion, it is used library research to find, collect, read, and analyze the books with no relevance to the research problem. The relevant references then is compiled, analyzed, so as obtained as conclusion. To achieve success in the educational process, the material in the book Al Akhlaq Lil Banat can be used as a reference in order to achieve educational success. The material presented in this book is not only refers to the relationship between man and God (transcendental), but also on the relationship between humans (anthropocentric), such as morality to parents, relatives, neighbors, peers and also to the adab or ordinances, such manners visit, walking, traveling, and so forth.